An innovative light assisted production of acetic acid from CO2 and methanol: a first photocatalytic approach using a reusable cobalt(ii) molecular hybrid at atmospheric pressure - Saini, Sandhya; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Ray, Anjan; Jain, Suman L. (Green Chemistry, 2021)
Acetic acid is an important commodity chemical that is produced either by fermentation processes, or more commonly, through chemical routes such as methanol carbonylation with CO and H-2, acetaldehyde oxidation, or hydrocarbon oxidation. More recently, methanol hydrocarboxylation with CO2 and H-2 under thermal catalytic conditions has attracted interest. The synthesis of acetic acid from easily available CO2 is of great significance yet rarely reported. The present paper describes the first photocatalytic approach for the synthesis of acetic acid from methanol and CO2 under ambient reaction conditions without using molecular hydrogen. The maximum conversion of methanol achieved is 60% with a selectivity of 81% towards acetic acid using an octa-sulfur bound cobalt phthalocyanine (CoPc/S8) photocatalyst without an additional sacrificial electron donor. Product analysis, controlled experiments and DFT calculations suggest the formation of methylene carbene as a reactive intermediate. The developed methodology represents a potentially exciting approach for synthesizing acetic acid utilizing CO2 in a sustainable manner.

Process development for crystalline xylitol production from corncob biomass by Pichia caribbica - Dasgupta, Diptarka; Sidana, Arushdeep; Sarkar, Bipul; More, Snehal; Ghosh, Debashish; Bhaskar, Thallada; Ray, Anjan (Food and Bioproducts Processing, 2022)
Xylitol, a commodity chemical, is widely used in nutraceutical and pharmaceutical formulations. Microbial xylitol production is a promising alternative to mitigate current industrial practice issues and offers an environment-friendly sustainable conversion route. This study demonstrates a bioprocess for xylitol production from corncob using a mesophilic yeast Pichia caribbica. Corncob was hydrolyzed by dilute acid and steam explosion to recover fermentable xylose and used as the feed for xylitol production. Activated carbon treatment (3% w/v) completely removed the biomass-derived inhibitors furfural and hydroxymethyl furfural from the liquid hydrolysate. The fermenting yeast Pichia caribbica produced 124.1 +/- 0.45 g/L xylitol from the detoxified and concentrated corncob hydrolysate with a high yield of 0.80 +/- 0.02 g/g. The crystallized xylitol with 96.5% purity demonstrated no harmful effects on the cell line used as a control for the in-vitro toxicity studies. This proof of concept can be applied to help scale up for bio-refinery-based large-scale production of xylitol from corncob biomass.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass; Corncob; Detoxification; Fermentation; Toxicity analysis; xylitol

Sulfonated zinc phthalocyanine coating as an efficient and ecofriendly corrosion inhibitor for copper surfaces: an in silico led design and its experimental validation - Dekshinamoorthy, Amuthan; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Khatri, Praveen K.; Jain, Suman Lata; Ray, Anjan; Vijayaraghavan, Saranyan (Langmuir, 2023)
The current study highlights the successful integration of an in silico design with experimental validation to create a highly effective corrosion inhibitor for copper (Cu) surfaces. The synthesized sulfonated zinc phthalocyanine (Zn-Pc) is electrochemically characterized and demonstrates an impressive 97% inhibition efficiency, comparable to the widely used industrial corrosion inhibitor, BTA, for Cu surfaces. The corrosion inhibition is comprehensively analyzed through potentiodynamic polarization and impedance spectroscopy techniques, supported by their respective equivalent circuits. Furthermore, the sample undergoes thorough characterization using scanning electron microscopy, energy-dispersive X-ray analysis, X-ray photoelectron spectroscopy, contact angle measurements, and atomic force microscopy. Density functional theory calculations reveal that sulfonated Zn-Pc exhibits the highest interaction energy, underscoring its exceptional inhibition properties. These results open possibilities for utilizing computational methods to design and optimize corrosion inhibitors for protection of Cu surfaces.